KOMUNIKASI BISNIS, DAN MOTIVASI BERPRESTASI SEBAGAI FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN - Imam Santoso; Witler Slamat Halomoan Silitonga (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
The objective of this research to obtain information relating to the influence business communication , achievement motivation on performance of Perumnas marketing employees. This Research has been carried out using regretion analysis.in this study, 320 employees of the third level housing company in jabotabek as population were randomly selected as analysis unit of along with 78 samples along with the thirfd caracteritics study. The results showed that (1) communication business has significant effect on the employees work performance (2) achiement motivation has sigficant effect on employee work performance (3) communication business and achiement motivation has significant effect on the employees work performance. The result of the studies show that business communication, achievement motivation is an important determinant of the employee work performance.Based on these findings it can be concluded that any change or variantions that occur in the work performance of perumnas employees have been influenced by business communication and achievement motivation Therefore business comunication, and achievement motivation must be included in the strategic planning of human resource development in increasing the work performance of perumnas employees, but need to consider other varables needed to work performance is influenced by variation in business communication , and achievement motivation Keywords: .